The Effect of Good Corporate Governance on Investment Decisions in the Trade, Service and Investment Sector Listed on the IDX in 2013-2017 - Risma Wulandari; Sriyono Sriyono (International Consortium of Education and Culture Research Studies, 2021)
This study aims to determine the Effect of Good Corporate Governance on Investation Decision in the Trade, Service and Investment Sectors listed on the Indonesia Stock Exchange in 2013-2017.This study uses quantitative descriptive research using multiple linear regression analysis techniques and uses Program Eviews 10. The hypothesis in this study is that there is a partial and simultaneous influence on Good Corporate Governance and Corporate Social Responsibility as an independent variable on ROE as the dependent variable.The research results obtained are for partial hypothesis testing of the Board of Directors does not have a significant effect on ROE, the Board of Commissioners has a significant effect on ROE, the Audit Committee, CSR has no significant effect on ROE. While simultaneously the Board of Directors, Board of Commissioners, Audit Committee and CSR have a significant effect on ROE